Enhanced sonocatalytic degradation of bisphenol A with a magnetically recoverable biochar composite using rice husk and rice bran as substrate - Chu, Jae Hun; Kang, Jin Kyu; Park, Seong Jik; Lee, Chang Gu (Journal of Environmental Chemical Engineering, 2021)
Ultrasound (US)-assisted heterogeneous Fenton process can be effective in treating organic compounds. In this study, magnetic biochars were synthesized as a heterogeneous Fenton catalyst for bisphenol A (BPA) removal using rice bran (RB-MBC), rice husk (RH-MBC), and their mixture (RBH-MBC). The synthesized catalysts were characterized using a field emission scanning electron microscope/energy dispersive X-ray spectrometer, N2 adsorption-desorption, and X-ray diffractometry. The magnetic biochars had round crystalline maghemite grains with well-developed pores. The BPA degradation efficiency of RB-MBC (94.25%) was compared with that of RH-MBC (94.25%) and RBH-MBC (94.25%) in heterogeneous sono-Fenton triple system as well as single (RB-MBC (adsorption): 10.46%, H2O2: 2.45%, US (sonolysis): 1.45%) and dual (RB-MBC + US: 14.46%, RB-MBC + H2O2 (heterogeneous Fenton): 13.46%, H2O2 + US: 3.45%) system. The enhanced hydroxyl radical generation in the heterogeneous sono-Fenton process was quantified via photoluminescence analyses. According to artificial neural network analysis, the significance of the operating parameters for BPA degradation was in the following order: initial H2O2 concentration (27.79%), initial BPA concentration (20.87%), ultrasonic power (19.38%), RB-MBC dose (19.18%), and solution pH (12.78%). These findings can facilitate an understanding of the application of magnetic biochar derived from rice bran as a heterogeneous Fenton catalyst for degrading organic compounds under US irradiation.
Keywords: Degradation efficiency; Field emission scanning electron microscopes; Heterogeneous fenton; Hydroxyl radical generation; Operating parameters; Photoluminescence analysis; Sonocatalytic degradation; Ultrasonic power; Artificial neural network; Fenton oxidation; Magnetic biochar; Rice bran; Rice husk; Sonolysis